2015
DOI: 10.1007/s10903-015-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-utilization of the Pap Test Among Women with Frequent Health System Contact

Abstract: Despite improvements in health access, many underserved women abstain from cervical cancer screening. A self-administered questionnaire was used to identify factors determining whether medically underserved women attending a safety net health system regularly are screened for cervical cancer. Approximately 11 % of study subjects had never received a Pap test despite an average of nearly four clinic visits in the preceding 12 months. Never screeners were significantly younger, more likely to be Hispanic, non-U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…This finding is similar to a study reporting on associations between male partners wanting women to receive regular screening and women's likeliness to participate (Ogunwale et al 2016). Women who needed someone else´s permission to attend screening were less likely to attend screening than women who did not.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is similar to a study reporting on associations between male partners wanting women to receive regular screening and women's likeliness to participate (Ogunwale et al 2016). Women who needed someone else´s permission to attend screening were less likely to attend screening than women who did not.…”
Section: Discussionsupporting
confidence: 87%
“…This has also been reported elsewhere (e.g. Byrd et al 2007;Mutyaba et al 2007;Ogunwale et al 2016). That 28 % of Roma women and 8% of non-Roma women needed permission to attend screening ( Supplementary Table 1) suggests that an information strategy that includes men could potentially be useful.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Within the U.S., Hispanic women are less likely to receive Pap smears than other ethnic groups, even after controlling for barriers to care [11]. Furthermore, several recent studies have found that a significant proportion of the women non-compliant with screening report that they have never been screened despite regular visits to their primary care provider for other clinical indications [12][13][14]. Thus, efforts to address barriers to cervical cancer screening, particularly among high risk populations, will remain important for the foreseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…By using an effective screening service in the last 4 decades-a consequence of the introduction of the Pap test in 1941-the United States has reduced its incidence of cervical cancer by 70%. However, women who have never been screened with a Pap smear account for 29-50% of all cervical cancer diagnoses despite access to healthcare in developed countries (Ogunwale et al, 2016).…”
Section: Introductionmentioning
confidence: 99%